2020
DOI: 10.1007/s10973-020-10383-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of different innovative turbulators on the turbulent flow field and heat transfer of a multi-phase hybrid nanofluid

Abstract: This study investigates the heat index by combining factors affecting the enhancement of heat transfer, including the modeling of three turbulators with 3D innovative geometries, hybrid nanofluid, including Cu and Al 2 O 3 , and high Reynolds numbers. Using the Eulerian method and the phase-coupled simple algorithm, a 3D tube in which turbulators with different sizes were embedded along with a hybrid nanofluid with a two-phase view were investigated. The geometry of rectangular turbulator is a = 1 cm, b = 3, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Doubleperforated inclined elliptic (DPIE) ortex generators with d/ b = 0.25 and = 25 achieve the highest thermal performance parameter (η) of 1.849 at Re = 16,000.They have several advantages over active methods, including relative simplicity, lower manufacturing costs, and lower maintenance and repair costs (Gokulnathan, 2021;Wu, 2011;Liang et al, 2020).In passive techniques, increasing flow turbulence is the key to improving heat transfer, while pressure drop or friction factor is typically kept as low as possible. The most commonly used turbulators to improve thermal efficiency are baffles, ribs, winglets, perforated turbulators, louvered strips, inclined elliptical strips, twisted tapes , and different helical inserts, rectangular turbulators (Mahani, 2021), ring inserts, and springs (Kareem, 2015;Liu, 2013). Hatami et al (2015) used a turbulator of delta winglet to improve heat recovery from a diesel engine exhaust.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Doubleperforated inclined elliptic (DPIE) ortex generators with d/ b = 0.25 and = 25 achieve the highest thermal performance parameter (η) of 1.849 at Re = 16,000.They have several advantages over active methods, including relative simplicity, lower manufacturing costs, and lower maintenance and repair costs (Gokulnathan, 2021;Wu, 2011;Liang et al, 2020).In passive techniques, increasing flow turbulence is the key to improving heat transfer, while pressure drop or friction factor is typically kept as low as possible. The most commonly used turbulators to improve thermal efficiency are baffles, ribs, winglets, perforated turbulators, louvered strips, inclined elliptical strips, twisted tapes , and different helical inserts, rectangular turbulators (Mahani, 2021), ring inserts, and springs (Kareem, 2015;Liu, 2013). Hatami et al (2015) used a turbulator of delta winglet to improve heat recovery from a diesel engine exhaust.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the numerical results predicted by the SST k‐ω model were in better agreement with the experimental data for the droplet removal efficiency than the enhanced Reynolds stress model. Mahani et al [ 30 ] investigated a 3D tube embedded with turbulators by using the Eulerian method and the phase‐coupled simple algorithm. They found that the numerical results were close to the experimental results.…”
Section: Introductionmentioning
confidence: 99%